Research Progress on Therapeutic Effect and Mechanism of Propolis on Wound Healing. (21st July 2022) - Yang, Juan; Pi, Anjuan; Yan, Lele; Li, Juan; Nan, Sha; Zhang, Jing; Hao, Yuhui
Abstract : Propolis is a kind of reduct collected by bees from various plant sources. Because propolis is a mixture, it has a variety of biological activities, excellent anti-inflammatory and bactericidal effects. Especially in the treatment of infectious wounds, acute wounds, burns, and scalds and promoting wound healing, more and more scientists began to apply it to the research field of wound healing. The standard preparation of propolis combined with other compound components has a safer and less toxic effect in the treatment of trauma. In order to more effectively use propolis products in wound treatment. This paper reviews the effect and treatment mechanism of propolis on different types of wound healing, as well as the synergistic effect of propolis and other compounds, in order to provide ideas for the further exploration of the biological activity and pharmacological function of propolis in the future, as well as its in-depth development in the field of wound healing. It will also provide a theoretical reference for the further development and utilization of propolis.